Profissionais de enfermagem do setor da emergência: um estudo exploratório - Azevedo, Andressa Storti Neves de (2007)
In hospitals, work division is the reproduction of the development according to the model of capitalist production. As Nursing is inserted in hospital settings and the increase of its complexity; this institution becomes a company of accounting services. Nursing work is accomplished by different categories of professionals that suffer tension, besides long work days, short remuneration, double job and insalubrity conditions of the work environment, resulting absenteeism. Objective: The objective of this study was to characterize Nursing professionals performing in the Emergency section of a school general hospital in the municipality of São Jose of Rio Preto, in the year of 2006 according to the function and section that perform, the socioeconomic and health conditions of this population. Material and method: A questionnaire was applied to the Nursing technicians and auxiliaries of the Emergency section. With the data, a database was constructed, and tabulations were produced for information that characterized these professionals. Results: Most of the studied population has been working more than 8 hours a day, mainly during the day, and 82.8% were Nursing auxiliaries, while only 9.2% were hired as Nursing technician. Female sex was predominant, and 46.0% were aged between 21 and 30 years. We observed that 46% lived in union; 44.8% did not have children; 52.9% were catholic. Finally, 72.4% reported to work only in one job and 75.8% were feeling well in relation to the health. It was surprising the fact that 34.5% of these professionals were overweighed. Conclusion: We concluded that this professional category is highly female, working more than eight hours a day in an environment considered unhealthy; in spite of this, they claimed to feel well in relation to their health.